The virtuous manager - Moore, Geoff (Henry Stewart Talks, 2011)
How we might re-imagine management and the morality of management, The moral problem of managers in capitalist business organisations, A business organisation as a combination of a practice and an institution, Virtuous business organisations and virtuous managers, The virtues of a virtuous manager, Practical applications